Erratum: Demographic Profile and Risk Factors for Dry Eye - KC, Shiva Raj (Nepalese Medical Journal, 2019)
The online version of the “Demographic Profile and Risk Factors for Dry Eye”(Basnet, P.; Basnet, A.; Karki, P. Demographic Profile and Risk Factors for Dry Eye. NMJ 2018, 1, 9-11. DOI: https://doi.org/10.3126/nmj.v1i1.20391) has been updated. In the publication study period was missed. Study period "from 1st June 2017 to 30th November 2017" has been added.